Model Sistem Peran Teknologi dan Informasi Terhadap Pertahanan Bisnis di Indonesia - Tati Herlia (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
Business is an activity carried out and carried out by someone or a group of people or companies in the form of services or goods to obtain profits or profits. Nowadays businesses are starting to grow and develop rapidly in Indonesia in the creative economy industry sector. Creative economy is an economy that is based on high creativity with a touch of innovation to produce new and different quality products. Today's business trends are more companies in the creative economy. This is because the creative economy is faster than other industries. The fastest growing creative industry and development is in the field of information technology. The cause of the creative industry in the field of technology is growing rapidly, because the world is now entering the information technology era. So today's business does not recognize space and time. In addition, business is easy to do and easily accepted by consumers. This, if left unchecked, will disrupt national economic stability so that it is necessary to make a System Model for the Role of Information Technology towards Business Defense in Indonesia.